Effect of community-based nutritional counseling intervention on children's eating habits. Issue 30 (30th July 2021) - Dike, Ibiwari Caroline; Ebizie, Elizabeth N.; Chukwuone, Chiamaka Adaobi; Ejiofor, Ngozi Juliana; Anowai, Chinwe Christiana; Ogbonnaya, Ezeda Kalu; Ugwu, Eunice Ifenyinwa; Nkechinyere, Udeagha Scholastica; Chigbu, Eberechukwu Francisca; Ezeaku, Margret N.; Nnadi, Grace Chinyere; Ihuoma, Ekomaru Chinyere; et al.
Abstract: Aim: This study aimed to assess the outcome of community-based nutritional counseling interventions on eating habits of rural-dwelling children. Methods: A group-randomized trial design was used in this study. A total of 108 rural-dwelling children from a community in the Enugu North agricultural zone, Enugu State, who participated in the study. The children were randomly assigned to 2 groups: the treatment group (n = 54) and the no-treatment control group (n = 54). The child eating behavior questionnaire was used for data collection. Parents of the participating children within each study group completed the child eating behavior questionnaire at 3 time points. The data collected were analyzed using an independent sample t test at a probability level of .05. Result: The outcome of the study showed that the children's eating habits in the treatment group improved positively following the community-based nutritional counseling intervention. The positive gain from exposure to the community-based nutritional counseling intervention program was sustained during follow-up for children in the treatment group compared with the no-treatment group. Conclusion: The community-based nutrition counseling intervention carried out among children in rural communities had a positive adjustment in children's eating habits. The intervention requires the constant collaboration of professional childhood educators, caregivers, home economists, school staff, healthcare specialists, families, and the children themselves. Furthermore, there is a need for future long-term evaluations of the effects of community-based nutritional counseling interventions on children's nutrition and eating habits.